Comparison of Treatment Outcomes among Tuberculosis Patients with HIV and Without HIV Infection in a Metropolitan City - Madhavi Kamble; Yasmeen K Kazi (Medsci Publications, 2019)
Background: Tuberculosis (TB) is a major public health problem. Along with HIV infection, it forms a deadly combination and those with these diseases are seen to have unfavourable outcomes. Objectives: 1)To study the clinical profile of TB patients with HIV and without HIV co- infection. 2) To find the treatment outcome among the groups. 3)  To compare treatment outcomes of patients between the groups. 4) To assess associated factors influencing treatment outcome in both groups. Methodology: The study group included sero positive Tuberculosis patients, while the control group included sero negative Tuberculosis patients. They were enquired about their demographic profile, socio-economic status, past and present TB history including their treatment details and treatment outcome. Additional information regarding the basic CD4 count diagnosis and Anti-Retroviral Therapy (ART) was collected from the study group. Important Findings: Tuberculosis was more commonly seen in lower socioeconomic group, less educated and economically most productive group. Common symptom seen was fever, cough and weight loss. More prominent signs and symptoms were seen in seropositive patients. Weight gain was more significant in the control group. Treatment outcome was favourable among sero negative patients.  Conclusion: Treatment outcome of tuberculosis patients on DOTS regimen depends on the HIV status of the patient.